Quasilinear description of electron cloud dynamics in the solar corona plasma - Mel’nik, V.N.; Kontar, E.P.; Lapshin, V.I. (Вопросы атомной науки и техники, 2000)
In this study, we consider dynamics of maxwellian electron cloud with the temperature significantly exceeding that of surrounding plasma. We investigate the transition from initially free electron propagation to a quasilinear one. We show qualitatively and quantitatively that only a small part of the cloud propagates into a plasma, whereas the main part of electrons is concentrated in the place of injection. These electrons turn out to be locked by the Langmuir turbulence generated by the electrons left that region.